Promyelocytic sarcoma of the right humerus: an unusual clinical presentation with unique diagnostic and treatment considerations. Issue 11 (29th September 2017) - Sawhney, Sameer; Holtzman, Noa G.; Davis, Derik L.; Kaizer, Hannah; Giffi, Victoria; Emadi, Ashkan; Koka, Rima
Key Clinical Message: Promyelocytic leukemia is a known medical emergency and requires rapid diagnosis and expedient therapy with differentiating agents. We present an unusual case in which the diagnosis is based on a fine needle aspirate of a humeral mass. Despite lack of systemic involvement, the sarcoma responded to traditional differentiation agents. Abstract : Promyelocytic leukemia is a known medical emergency and requires rapid diagnosis and expedient therapy with differentiating agents. We present an unusual case in which the diagnosis is based on a fine needle aspirate of a humeral mass. Despite lack of systemic involvement, the sarcoma responded to traditional differentiation agents.